Risk factors for the development of macular edema in children with uveitis - Friling, Ronit; Berliner, Ori; Eiger-Moscovich, Maya; Chen, Yi-Hsing; Tomkins-Netzer, Oren; Kramer, Michal (Frontiers in Ophthalmology, 2023)
Aim To determine the risk factors for macular edema (ME) in children with uveitis. Methods A retrospective study was conducted of 150 pediatric patients (264 eyes) with uveitis attending 2 tertiary medical centers. Data were collected from the medical files on demographics, type of uveitis, etiology, clinical findings, treatment, and time to development of ME. Risk factors for the development of ME were identified. Results ME developed in 63 eyes (23.9%) over a mean period of 15.3 ± 2.95 months from diagnosis of uveitis, at a rate of 0.08 eyes per eye-year. On univariate analysis, risk factors for the development of ME were the non-anterior location of the inflammation (p=0.002), band keratopathy (p <0.0001), posterior synechiae (p=0.003), cataract (p=0.002), and vision impairment at presentation (p <0.0001). On multivariate analysis, non-anterior uveitis, which includes intermediate, pan, and posterior-uveitis, and vision impairment retained significance as independent risk factors of ME. Conclusion Within the pediatric population with uveitis, non-anterior location is associated with the highest risk of ME, followed by the presence of complications, such as band keratopathy and posterior synechiae. These findings indicate a need for close follow-up in children with uveitis for early detection of ME.